Community Empowerment at the Sabatang Bungo Randai Studio in Pasar Lalang, Kuranji District, Padang City - Cindy Jufrianda; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This research is motivated by the participatory and comprehensive community empowerment carried out at the Sanggar Randai Sabatang Bungo in Pasar Lalang, where the community is actively involved in every activity. This studio not only focuses on randai, but also provides training in traditional dance, silat, and musical instruments, thus providing wider opportunities for members to develop their interests and talents. These activities contribute to improving artistic skills, self-confidence, togetherness, cultural awareness, and providing economic support. This research uses a qualitative approach with a case study type. The research informants consisted of managers, facilitators, learners, and one community member. Data collection techniques were carried out through interviews, observation, and documentation, then analyzed using an interactive analysis model that includes data collection, data reduction, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources, techniques, and time. The results of the study indicate that community empowerment is implemented systematically through three stages: awareness, capacity building, and empowerment. These stages are able to increase community participation, develop skills and discipline, and provide opportunities for self-actualization and economic benefits. Overall, the studio not only functions as a space for cultural preservation, but also as an effective means of empowerment in strengthening local cultural identity and increasing community capacity.